2016
DOI: 10.1093/cercor/bhw075
|View full text |Cite
|
Sign up to set email alerts
|

eEF2K/eEF2 Pathway Controls the Excitation/Inhibition Balance and Susceptibility to Epileptic Seizures

Abstract: Alterations in the balance of inhibitory and excitatory synaptic transmission have been implicated in the pathogenesis of neurological disorders such as epilepsy. Eukaryotic elongation factor 2 kinase (eEF2K) is a highly regulated, ubiquitous kinase involved in the control of protein translation. Here, we show that eEF2K activity negatively regulates GABAergic synaptic transmission. Indeed, loss of eEF2K increases GABAergic synaptic transmission by upregulating the presynaptic protein Synapsin 2b and α5-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 97 publications
8
92
1
Order By: Relevance
“…Suppression of eIF2α phosphorylation corrected AD-associated cognitive and synaptic plasticity defects (17), indicating a crucial role of translation initiation dysregulation in AD pathogenesis. Mounting evidence suggests an important role for elongation regulation in cognition, with recent studies linking dysregulation of elongation factors with AD pathophysiology (15,(44)(45)(46)(47). Of note, a recent study showed a connection between eIF2 signaling and eEF2 phosphorylation in neurons (48).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of eIF2α phosphorylation corrected AD-associated cognitive and synaptic plasticity defects (17), indicating a crucial role of translation initiation dysregulation in AD pathogenesis. Mounting evidence suggests an important role for elongation regulation in cognition, with recent studies linking dysregulation of elongation factors with AD pathophysiology (15,(44)(45)(46)(47). Of note, a recent study showed a connection between eIF2 signaling and eEF2 phosphorylation in neurons (48).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking Mecp2 in GABAergic interneurons (Viaat-Cre;Mecp2) show reduced quantal GABA content and messenger RNA levels for GABA-synthesizing GAD65 and GAD67 (120). Mice lacking the synaptic vesicle protein synapsin I (SynI), implicated in ASD and epilepsy, show epileptic propensity, and neurons from these mice reexpressing a disease-related mutant SynI display reduced readily releasable pool of GABA-containing vesicles and stronger short-term depression (121), which may involve abnormally activated eEF2K/eEF2 signaling (122). Conditional deletion of ErbB4 in PV neurons causes reduced neuregulindependent GABA release in the prefrontal cortex and cognitive deficits that are rescued by diazepam (123), results in line with the increased seizure susceptibility observed in these mice (124,125).…”
Section: Interneuronsmentioning
confidence: 99%
“…In addition, high levels of p-eEF2 were also reported in a mouse model of Alzheimer’s disease (Li et al, 2005) and in brain material of patients affected by Alzheimer’s disease, suggesting a particular role of the eEF2K/eEF2 pathway in mental disorders. Moreover, the pharmacological and genetic inhibition of eEF2K was recently reported to be able to reverse the epileptic phenotype in a mouse model of human epilepsy (Heise et al, 2016). These data show a novel role of eEF2K in the regulation of brain network activity, providing a novel target for brain disorder treatment.…”
Section: Discussionmentioning
confidence: 99%